1999
DOI: 10.1111/j.1151-2916.1999.tb02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Cation Mixing of MgAl2O4 and ZnAl2O4 Spinel

Abstract: The kinetics of the site exchange reaction of Al 3+ cations between tetrahedral and octahedral sites in MgAl 2 O 4 and ZnAl 2 O 4 spinel in natural and synthetic powdered samples was determined by 27 Al MAS-NMR spectroscopy with a high-speed magic-angle-spinning probe using samples heattreated for different time periods. Three site fittings to the 27 Al NMR spectra, one tetrahedral site [4] Al and two octahedral sites ( [6] Al(1) and [6] Al(2)), reasonably reproduced the observed spectra. Among these three sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 18 publications
8
59
0
Order By: Relevance
“…However, the size of the peak indicates that the amount of inversion is very small. Kashii et al 30 found the same results, but they kept zinc aluminate at 900 C for 40 h in contrast to 800 C for 8 h used in this investigation. Furthermore, it is clear that there is no difference between the two preparation methods and that neither the temperature nor the calcining time does have a significant influence.…”
Section: Compositionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the size of the peak indicates that the amount of inversion is very small. Kashii et al 30 found the same results, but they kept zinc aluminate at 900 C for 40 h in contrast to 800 C for 8 h used in this investigation. Furthermore, it is clear that there is no difference between the two preparation methods and that neither the temperature nor the calcining time does have a significant influence.…”
Section: Compositionsupporting
confidence: 82%
“…28,29 Furthermore, NMR studies on the cation inversion in zinc aluminate, which is prepared via the solid-state synthesis route, confirm the virtual absence of inversion. 30 However, inversion has been found to some extent in zinc aluminate synthesized using a sol-gel method with alkoxides depending on the temperature. 14 …”
Section: Crystallographic Aspects Of Zinc Aluminatementioning
confidence: 99%
“…1 The interesting observation is that the milling brings about both a noticeable broadening and a shift (towards negative chemical shifts) of the (A) and [B] spectral lines, implying a change in the local atomic environments of Al 3+ (A) and Al 3+ [B] ions. This variation may be explained by the effect of a mechanically induced deformation of both AlO 4 tetrahedra and AlO 6 octahedra [4].…”
Section: Resultsmentioning
confidence: 98%
“…34,35) Different Q n species could coexist according to equilibria among Q n species which could be described as follows: 36) In the present work, the 29 Si MAS-NMR spectrum of all glass samples is deconvolved using Gauss-Deconvolution method by assuming contributions from structural units of Q 3 , Q 2 , Q 1 and Q 0 with the minimum correlation coefficient r 2 ≥ 0.99. 6,[36][37][38] The best-fit simulations are shown in Figs. The molar fractions of different structure units are related to the peak areas.…”
Section: Discussionmentioning
confidence: 99%